Cirrhosis of liver with third trimester of pregnancy: First report of two cases from Bangladesh - Al-Mahtab, Mamun; Rahman, Salimur; Podder, Provat Kumar; Khan, Mobin; Ahmed, Faroque; Barua, Uttam Kumar (Bangladesh Liver Journal, 2009)
Pregnancy is uncommon in cirrhosis. This is however not related to the aetiology of cirrhosis and rather results from hepatic dysfunction, reduced hepatic blood flow and reduced end organ sensitivity to sex hormones in these patients. Pregnancy in cirrhosis is associated with high incidence of foetal loss as well as higher maternal mortality both during pregnancy and in the post-partum period. Here we report two cases of cirrhosis of liver with third trimester of pregnancy for the first time from Bangladesh. doi: 10.3329/blj.v1i1.2626 Bangladesh Liver Journal Vol.1(1) 2009 p.51-54